Control pre-emergente y post-emergente dirigido sobre el complejo de malezas en el cultivo de maíz, en la zona de Ventanas - Chimborazo Peñafiel, Miguel Stalin (2017)
VIII. SUMMARY The present experimental work was carried out in the lands owned by Mr. Milton Chimborazo Carrasco, located in the "Los Angeles" parish, belonging to Ventanas, province of Los Ríos, with geographic coordinates of 79 ° 46 'west longitude and 01 ° 45 'south latitude and a height of 25 m. The soil is of loam - loam texture and good drainage. As seed material, seeds of the Dekalb 7088 hybrid were used; the objectives were to evaluate the preemergent and postemergence control applied to maize cultivation; identify the herbicide mixture and the most appropriate dose and analyze the results economically. The treatments studied were the mixtures of Paraquat + Diquat in doses of 1,5 L + 1,5 L and 2,0 L + 2,0 L; 2.4 D amine + Metsulfuron Methyl in doses of 1.0 L + 15 g and 1.5 L + 16 g applied in post emergence and Atrazine + Pendimetalin in doses of 2.0 kg + 3.0 L and 1.5 kg + 4.0 L used in pre-emergence plus an absolute control with mechanical control with three manual weeding. It was used the design of Complete Blocks Random, with seven treatments and three repetitions. To compare the means of treatment, the Duncan test was used at 5% probability. During the development of the experiment will be carried out the work of field preparation, planting, weed control, irrigation, fertilization, pest and disease control and harvesting. The data evaluated were toxicity index at 7 and 14 days after application of the products, weed control at 14 and 21 days after application of the products, plant height, ear length and ear diameter, number of weeds grains per ear, 1000 grains weight, performance and economic analysis. From the results obtained it was determined that the mixtures of herbicides applied caused little toxicity in the maize crop at 7 days, disappearing 14 days after the application of the products; the best weed control was recorded with the Paraquat + Diquat mixture, in doses of 1,5 L + 1,5 L and 2,0 L + 2,0 L applied in postemergence; the application of the herbicide mixtures influenced to obtain higher plant height compared to the mechanical control with three manual weeds; the length and diameter of ear excelled with the mixture of Paraquat + Diquat; the highest number of grains per ear was achieved by the application of 2.4 D amine + Metsulfuron Methyl, in doses of 1.5 L + 16 g and the weight of 1000 grains excelled using the same mixture but at doses of 1.0 L + 15 g and the highest grain yield and net benefit was obtained by applying Paraquat + Diquat in doses of 2.0 L + 2.0 L with 6078.0 kg / ha and $ 380.83.